Recidiva da tuberculose: análise dos fatores associados em um grupo de vigilância epidemiológica do estado de São Paulo - Rodrigues, Isabela Cristina (2014)
Background: Tuberculosis (TB) is a disease caused by Mycobacterium tuberculosis transmitted by aerosol. It is a curable disease when observing the basic principles of drug therapy and the proper operation of the treatment. Recurrence is the appearance of the disease in its active form, after completing a treatment and cure for discharge. Aim: To investigate risk factors for TB recurrence in cases reported by GVE XXIX/São José do Rio Preto/SP between 1996-2012. Methods: A case control study was conducted with TB patients recorded in the electronic state surveillance system. Controls were selected among TB patients who were treated, cured and did not experience a recurrence. Cases and control were paired by treatment year, municipality of residence and clinical presentation. The risk factor for TB recurrence were investigated through odds ration with 95% of confidence interval. Results: 376 cases were selected as the study subjects. Factor to TB recurrence were: gender male; clinical and epidemiological diagnostic confirmation; additional tests not performed; co-infection with HIV, chemical dependency and Diabetes Mellitus; unfavorable outcome to the 7th month; hospitalizations during the treatment; bacilloscopies control unrealized. Conclusions: Epidemiologial surveillance should be alert to the TB recurrences and it is associated factor, sharing responsibility with the municipalities to rethink the attention offered to severe cases, which presente comorbidities and poor clinical status, proposing changes that aimed the effective control of the disease in this population at the regional level.